A pseudospectral method for budget-constrained infinite horizon optimal control problems - Burtchen Angie; Lykina Valeriya; Pickenhain Sabine (ESAIM: Proceedings and Surveys, 2021)
In this paper a generalization of the indirect pseudo-spectral method, presented in [17], for the numerical solution of budget-constrained infinite horizon optimal control problems is presented. Consideration of the problem statement in the framework of weighted functional spaces allows to arrive at a good approximation for the initial value of the adjoint variable, which is inevitable for obtaining good numerical solutions. The presented method is illustrated by applying it to the budget-constrained linear-quadratic regulator model. The quality of approximate solutions is demonstrated by an example.